Effect of Tramadol (μ-opioid receptor agonist) on orthodontic tooth movements in a rat model. - M Rashidpour; M S Ahmad Akhoundi; T Hosseinzadeh Nik; Ar Dehpour; M Alaeddini; E Javadi; H Noroozi (Tehran University of Medical Sciences, 2012)
Tramadol is a synthetic analgesic of opioids which has more flexible mechanisms of action than typical opioids. Since it has been reported in previous study that typical opioids like morphine can affect the bone homeostasis, it is worthwhile to examine the effects of tramadol on tooth movement. In this study we investigated effects of tramadol on orthodontic tooth movement in rats.30 male wistar rats were selected and received orthodontic appliance. 3 groups were designed based on the substance that they received daily injections of during a 2-week orthodontic treatment. 1. Control group with no injection.2.Control group with normal saline injection.3. the tramadol group. After the two-week treatment period the amount of tooth movement were measured in all the groups. Also the histological analysis was performed assessing the root resorption, osteoclasts numbers and bone resorption.The amount of tooth movement was not significantl in the tramadol group comparing to the other groups (P>0.05).The results of 3 histological parameters (amount of root resorption, osteoclastic numbers and bone resorption) were statistically insignificant (P>0.05).Tramadol as an atypical opioid does not interfere with the process of bone remodeling and tooth movement in rat. Tramadol does not affect osteoclastic activity and bone resorption and it does not cause to change the resulted root resorption either.